Close correlation between season of birth and the prevalence of bronchial asthma in a Taiwanese population. - Wei-Chiao Chang; Kuender D Yang; Man-Tzu Marcie Wu; Ya-Feng Wen; Edward Hsi; Jen-Chieh Chang; You-Meei Lin; Ho-Chang Kuo; Wei-Pin Chang (PLoS ONE, 2013)
BACKGROUND: Bronchial asthma (BA), atopic dermatitis (AD), and allergic rhinitis (AR) are common allergic diseases. Environmental factors were indicated to influence the development of allergic diseases. OBJECTIVE: To evaluate the correlation between the month of birth and the prevalence of allergic diseases in Taiwan. METHODS: Data from 104,455 children were collected from the National Insurance Research Database of Taiwan. Subjects were identified by at least two service claims for ambulatory care or one claim for inpatient care. All of the enrolled patients were aged 7∼15 years in 2010. In a bio-clinical data analysis, total immunoglobulin E (IgE) and ImmunoCAP™ allergen data (CAP) from mothers and infants were collected in a medical center in Taiwan. Correlations between children's allergic factors and the season of birth were assessed. RESULTS: A significant difference in the prevalence of BA according to the month of birth (Χ(2) = 18.2, p<0.001) was found in the Taiwanese population. The fewest schoolchildren with were born in May (7.21%), and the most were born in October (10.59%). However, no tendency for the prevalence of AD (Χ(2) = 4.6, P = 0.204) or AR (Χ(2) = 4.3 P = 0.229) was found. In addition, we found that children born in autumn (August to October) had a higher prevalence of BA compared to those born in spring (February to April) (odds ratio: 1.13; 95% confidence interval: 1.05∼1.21). In a bio-clinical data study, markers of maternal and childhood allergies including IgE and CAP were detected in a risk analysis section. Children who were born in autumn had higher levels of CAP and total IgE. CONCLUSIONS: The findings of this study showed that the month of birth was closely correlated with the prevalence of BA and higher levels of CAP and IgE.